Effect of Lifestyle Modification with Metformin on Serum Chemerin Concentration of Metabolic Syndrome Subjects - Dharma Lindarto; Brama Ihsan Sazli (TALENTA Publisher, Universitas Sumatera Utara, 2019)
Chemerin is adipokine that plays an important role in macrophage infiltration into adipose tissue and may contribute to inflammation development and insulin resistance. This study aimed to determine the effect of lifestyle modification with and without metformin on chemerin in metabolic syndrome. Forty-five metabolic syndrome subjects (IDF-2005) were randomly assigned to one of the two groups: placebo group (n=22) and metformin group (n=23). Both groups underwent a 12-week lifestyle modification (diet and moderate aerobic-exercise). Only 40 participants (placebo group n=20 and metformin group n=20) completed the survey whereas 5 participants dropped out of the study. After their lifestyle was modified, body weight, BMI, WC, and chemerin decreased significantly (p<0.001) in both groups. Moreover, there was a significant difference between both groups in body weight, BMI, and WC (p<0.05) but not for chemerin. Thus, lifestyle modification with metformin improved BW, BMI, WC on metabolic syndrome, and there was no decrease significantly of chemerin between placebo and metformin groups. Further investigations should be done to confirm the effect of lifestyle modification and metformin on chemerin after an extended follow-up period.